Бережок: стихи и рассказы / В. Т. Коржиков - Коржиков Виталий Титович; Коржиков Виталий Титович (Малыш, 1989)
Экземпляры: Селтинская детская библиотека (20230726) / Инвентарный номер: 142390 / Авт.знак: К 65 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6